Are CEOs Rewarded for Luck? Evidence from Corporate Tax Windfalls - ANDREANI, MARTINA; ELLAHIE, ATIF; SHIVAKUMAR, LAKSHMANAN (Journal of Finance, 2025)
ABSTRACT Focusing on the one‐off tax gains and losses (i.e., windfalls) associated with the 2017 Tax Cuts and Jobs Act, we reexamine whether CEOs are rewarded for luck. We find that weakly monitored CEOs are compensated for the windfall tax gains but not penalized for the corresponding tax losses. No such pattern is observed for CEOs facing greater pay scrutiny. The pay for windfalls cannot be explained as rewards for CEOs’ efforts, talents, political activities, or as firms sharing their tax gains with all executives. The results are more consistent with rent extraction by CEOs facing weak pay scrutiny.